2010
DOI: 10.1038/jid.2010.147
|View full text |Cite
|
Sign up to set email alerts
|

Detection of Human Papillomavirus DNA in Plucked Eyebrow Hair from HIV-Infected Patients

Abstract: abnormality in DCS. Although the function of the CLE is still unclear, a role as a necessary scaffold for the lamellar bilayer organization is likely (Uchida and Holleran, 2008). Thus, CLE deficiency, coupled with disorganization of extracellular lamellar bilayers, likely merge to provoke the barrier abnormality in NLSDI (see Supplementary Figure S2 online). Finally, to overcome this metabolic disadvantage in forming the epidermal permeability barrier, epidermal proliferation likely increases, which in turn re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
0

Year Published

2012
2012
2016
2016

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 15 publications
1
5
0
Order By: Relevance
“…Although different procedures have been used for assessing the HPV DNA prevalence in human skin, including swab samples and plucked hairs, plucked eyebrow hairs are the most used. 5,[12][13][14] As expected, b-HPV types were predominant. Among b-HPV types, HPV 38, 5, 24, 17, 12, 23 and 37 were harboured by more than 15% of patients irrespective of the treatment used.…”
Section: Hpvsupporting
confidence: 81%
See 4 more Smart Citations
“…Although different procedures have been used for assessing the HPV DNA prevalence in human skin, including swab samples and plucked hairs, plucked eyebrow hairs are the most used. 5,[12][13][14] As expected, b-HPV types were predominant. Among b-HPV types, HPV 38, 5, 24, 17, 12, 23 and 37 were harboured by more than 15% of patients irrespective of the treatment used.…”
Section: Hpvsupporting
confidence: 81%
“…We may suggest that anti‐TNF‐α treatment was not immunosuppressive enough to promote cutaneous HPV infection. However, previous studies found that cutaneous HPV DNA persistence was not significantly associated with immunosuppressive treatment (renal transplant recipients) . We cannot exclude that long‐term treatment with TNF inhibitors might be associated with modification in HPV DNA prevalence.…”
Section: Introductionmentioning
confidence: 67%
See 3 more Smart Citations